Unraveling the dominance of intrinsic catalytic activities over electrical properties in electrocatalytic performance of two-dimensional chromium chalcogenide nanosheets - Yang, Jiefu (2024)
In this study, we synthesized a new category of materials, 2D Cr2X3 (where X = S, Se, and Te), using an APCVD method. By leveraging the same space group and identical exposed facets of the as-synthesized Cr2X3 nanoflakes, we compared their catalytic performance for HER and electrical properties to unveil the contribution of electrical conductivity in the overall performance. A descending trend in HER activities from Cr2S3 to Cr2Se3, and Cr2Te3 was found, as evidenced by the increasing overpotentials and decreasing current densities at the same overpotential. Interestingly, electrical properties showed an improving trend from Cr2S3 to Cr2Se3, and Cr2Te3, as revealed by IDS-VG and IDS-VDS tests based on FET devices, respectively. The primary factor affecting overall catalytic performance was found to be intrinsic catalytic activities rather than electrical properties, as supported by DFT calculations. These insights emphasize that the focus of harnessing intrinsic catalytic activities when exploring 2D electrocatalysts.